Penerapan Karya Hand Lettering Digital dengan Memadukan Motif-Motif Flora Bunga Anggrek - Muhammad Nur Huda; Raden Burhan Surya Nata Diningrat (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study examines the application of digital hand lettering combined with orchid floral motifs as an effort to create aesthetic and innovative visual artwork. The aim of this research is to explore digital hand lettering techniques and blend them with flora-based design elements, specifically orchids, which hold high artistic value and strong cultural symbolism. The research method used is qualitative with a descriptive approach, where data is collected through a literature review on hand lettering. The findings indicate that integrating orchid motifs into digital hand lettering not only enriches the visual appeal of the artwork but also adds unique and distinctive aesthetics. The resulting creations from this application have great potential for use across various media, such as posters, invitations, and commercial product designs. The conclusion of this study emphasizes that the application of digital hand lettering with orchid motifs can serve as an intriguing alternative in modern graphic design, contributing to the development of creativity and innovation in the creative industry.